Extreme intraspecific divergence in mitochondrial haplotypes makes the threespine stickleback fish an emerging evolutionary mutant model for mito-nuclear interactions - Beck, Emily A.; Bassham, Susan; Cresko, William A. (Frontiers in Genetics, 2022)
Mitochondrial DNA is primarily maternally inherited in most animals and evolves about 10 times faster than biparentally inherited nuclear DNA. Mitochondrial dysfunction (mt-dys) arises when interactions between the co-evolving mitochondrial and nuclear genomes are perturbed in essential processes like Oxidative Phosphorylation (OXPHOS). Over time mt-dys can lead to mitochondrial diseases (mt-diseases) which are surprisingly prevalent and include common diseases such as Alzheimer’s, Parkinson’s, and diabetes. Unfortunately, the strong impact that intraspecific mitochondrial and nuclear genetic variation has on mt-disease complicates its study and the development of effective treatments. Animal models have advanced our understanding of mt-disease but their relevance to human conditions is often limited by their relatively low nuclear genetic diversity. Many traditional laboratory models also typically have a single mitochondrial haplotype (mitotype), in stark contrast to over 5,000 mitotypes in humans worldwide. The threespine stickleback fish has an evolutionary history that has made it a favorable evolutionary mutant model (EMM) for studying mito-nuclear interactions and possibly mt-diseases. EMMs are species with naturally evolved states that mimic maladaptive human diseases. In threespine stickleback, a period of isolation followed by introgression of the mitochondrial genome from a sister species, resulted in the maintenance of two distinct mitochondrial haplotypes which continue to segregate within many populations of wild stickleback. The existence of two mitogenomes segregating in numerous genetically diverse populations provides a unique system for exploring complex mito-nuclear dynamics. Here we provide the first complete coding region assemblies of the two threespine stickleback mitotypes, whose mitogenomic divergence exceeds that of other mammalian models for mitochondrial disease and even that between ancient and modern humans. We find that divergence is not uniform across the mitogenome, but primarily impacts protein coding genes, and significantly impacts proteins in Complex I of OXPHOS. The full characterization of these highly divergent intraspecific mitotypes provides a foundation for the development of threespine stickleback as an EMM for mito-nuclear interactions.